PRIMARY OSTEOSARCOMA OF THE CALVARIA - PEKANAN, Patchrin; JAOVISIDTHA, Suphaneewan; SIRIWONGPAIRAT, Pimjai; PONGPECH, Sirintara; JIARAKONGMUN, Pakorn (The ASEAN Journal of Radiology, 2023)
Two cases of calvarial osteosarcoma was presented using images of plain films and CT scan. The first case was a 22-year-old female patient who had bony density mass of osteoblastic osteosarcoma at left frontal bone. The involved bone showed a mixed osteolytic and permeative lesions. The second case was a 4-year-old boy who had bony density mass of chondroblastic osteosarcoma at right temporal region. The involved bone also showed a mixed osteolytic and permeative lesions.